Pendidikan Karakter Siswa dalam Meningkatkan Kesadaran Kebersihan Lingkungan di MIN 3 Aceh Barat - Cut Nandia Rahmah; Hanifuddin Jamin; Abidah Abidah (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Character education is an effort made by an educator that aims to instill good behavior in students. In an effort to increase awareness of environmental cleanliness MIN 3West Aceh adopts a policy to implement character education that is aware of environmental cleanliness for students. This study aims to determine student character education in increasing awareness of environmental cleanliness at MIN 3 West Aceh. This study used a qualitative approach with data collection techniques using observation, interviews, and documentation, while data analysis techniques used descriptive methods with an inductive approach. The results of this study indicate that student character education in increasing awareness of environmental cleanliness at MIN 3 West Aceh includes (1) the existence of a self-development program including daily routine activities, spontaneous, exemplary, and school conditioning. (2) There are supporting and inhibiting factors for character education that are aware of environmental cleanliness in West Aceh MIN 3. The supporting factors include teachers, infrastructure, the role of parents and cooperation between the head of the madrasa, teachers and students. While the inhibiting factor is the unavailability of two types of segregated trash bins and the character of the students. (3) The strategies used in this research include carrying out routine activities, the cleanliness ambassador program, following good guidelines and monitoring and advising students when they make mistakes such as littering.